
用因式分解法解下列方程 (x-1)-2(2x-1)=0 9(x-2)²=4(x+1)² 2(t-1)²+t=1
1个回答
展开全部
1、(x-1)-2(2x-1)=0
(x-1)(1-2)=0
-(x-1)=0
1-x=0
x=1
2、9(x-2)²=4(x+1)²
9(x-2)²-4(x+1)²=0
(3x-6)²-(2x+2)²=0
(3x-6+2x+2)(3x-6-2x-2)=0
(5x-4)(x-8)=0
x₁=4/5 ,x₂=8
3、2(t-1)²+t=1
2(t-1)²+t-1=0
(t-1)(2t-2+1)=0
(t-1)(2t-1)=0
t₁= 1 t₂=1/2
(x-1)(1-2)=0
-(x-1)=0
1-x=0
x=1
2、9(x-2)²=4(x+1)²
9(x-2)²-4(x+1)²=0
(3x-6)²-(2x+2)²=0
(3x-6+2x+2)(3x-6-2x-2)=0
(5x-4)(x-8)=0
x₁=4/5 ,x₂=8
3、2(t-1)²+t=1
2(t-1)²+t-1=0
(t-1)(2t-2+1)=0
(t-1)(2t-1)=0
t₁= 1 t₂=1/2
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询